'Second-tier outpost'? Negative civic image and urban infrastructure development. (April 2019) - Sant, Stacy-Lynn; Mason, Daniel S.; Chen, Chen
Highlights: Proponents of sport and entertainment facilities use negative self-image of a city to argue for projects. Media framing can be used to understand discourse surrounding infrastructure development projects. The media frame projects as opportunities to advance cities within a perceived urban hierarchy Discourses of negative self-image may be damaging to entrepreneurial cities.